Malignant Phyllodes Tumor of the Breast with Metastasis to the Pancreas: A Case Report and Review of Literature - R. A. Amir; Rola S. Rabah; S. S. Sheikh (Case Reports in Oncological Medicine)
Phyllodes tumor (PT) is a rare tumor of the breast accounting for approximately 1% of all breast neoplasms. In 1838, J. Muller coined the term “cystosarcoma phyllodes” based on the leaf-like projections of the tumor extending into the cystic spaces and sarcomatous stromal growth. However, seeing as up to 70% of phyllodes tumors are benign, “cystosarcoma” was removed, and the tumor is now recognized simply as phyllodes tumor. It is mainly seen in females between the ages of 35 and 55. Although most phyllodes tumors are benign, malignant cases do uncommonly occur, 22% of which have distant metastasis typically to the lungs and bones. Rarely, this tumor metastasizes to other locations. Herein, we report a case of malignant phyllodes tumor with metastasis to the pancreas. According to our knowledge, only 3 case reports of pancreatic metastasis from malignant phyllodes tumor have been reported in literature thus far. We aim to increase awareness among physicians of this rare metastasic potential of the uncommonly encountered malignant phyllodes tumor.